2016
DOI: 10.5937/inovacije1604101s
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in environmentalism: A case study of Macedonian students

Abstract: Summary: This study focuses on the impact of gender on environmental worldview in a sample of Macedonian students. The sample used in the final analysis consisted of 448 Macedonian students from 7 elementary and high schools. Participants completed the New Ecological Paradigm scale (NEP; Dunlap et al., 2000). Empirical findings suggest that no firm and clear conclusions can be drawn about the effects of gender on (NEP) environmental concern in a sample of Macedonian students. Findings are discussed in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Most of gender and environmental studies have emphasized that there are variations between males and females regarding energy, environment knowledge, behavior, and contributions (Hunter et al, 2004;Sigmon et al, 1995;Srbinovski, 2017;Zelezny & Aldrich, 2000) and stressed that gender perspective as a critical factor in sustainable energy consumption (Slini & Pavlidou, 2016). The reason for gender differences in energy-saving behavior may be ingrained in complex nature.…”
Section: Gender Differences In Energy Landscapementioning
confidence: 99%
“…Most of gender and environmental studies have emphasized that there are variations between males and females regarding energy, environment knowledge, behavior, and contributions (Hunter et al, 2004;Sigmon et al, 1995;Srbinovski, 2017;Zelezny & Aldrich, 2000) and stressed that gender perspective as a critical factor in sustainable energy consumption (Slini & Pavlidou, 2016). The reason for gender differences in energy-saving behavior may be ingrained in complex nature.…”
Section: Gender Differences In Energy Landscapementioning
confidence: 99%
“…The assessment of cognitive, affective and skill variables, and particularly the latter, has not received equal attention. The affective and cognitive EE domains of students in the Republic of North Macedonia have been studied by Srbinovski (2005aSrbinovski ( , 2006Srbinovski ( , 2016 Srbinovski, & Zenki (2009), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the Macedonian students' higher NEP score is perhaps due to the fact that the Macedonian sample includes more girls than the Serbian sample (Table 2). But empirical findings suggest that no firm and clear conclusions can be drawn about the effects of gender on (NEP) environmental concern in a sample of Macedonian students (Srbinovski, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Attitudes, knowledge and action in relation to the environment in the Republic of Macedonia have been studied by: Abazi, Ismaili, and Srbinovski (2009); Idrizi, Srbinovski, Jonuzi, and Murati-Sherifi (2015); Ismaili, Abazi, and Srbinovski (2009); Ismaili, Srbinovski, and Sapuric (2014); Jonuzi (2009Jonuzi ( , 2012; Kundačina (1991); Srbinovski (2001Srbinovski ( , 2005aSrbinovski ( , 2005bSrbinovski ( , 2006Srbinovski ( , 2016, Srbinovski, Palmer, Ismaili, Abazi, and Zenki (2007), Srbinovski, Ismaili, and Abazi (2010b), Srbinovski, Ismaili, and Abazi (2011), Srbinovski, Ismaili, and Jonuzi (2013), Srbinovski, Idrizi, and Jonuzi (2014), Srbinovski, Ismaili, and Zenki (2014). According to these studies, in the last 20 years approximately 74% of Macedonian students have demonstrated pro-environmental attitudes, measured by 13-item, 5-point, two-way Likert-type scale instruments with values running along the strongly agree/strongly disagree continuum.…”
Section: Characteristics Of the Serbian And Republic Of North Macedonmentioning
confidence: 99%